EKSPLORASI FAKTOR KENDALA DAN STRATEGI IMPLEMENTASI REFORMASI PERPAJAKAN GUNA MENDORONG PENINGKATAN PENERIMAAN PAJAK DAN KEPATUHAN WAJIB PAJAK - Adi Santoso; NASHARUDDIN MAS; GUNARIANTO GUNARIANTO (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2022)
ABSTRACT The purpose of the research is to obtain empirical evidence in the form of propositions and existing models on the exploration of constraint factors and strategies for implementing tax reform to encourage increased tax revenue and taxpayer compliance. Intensive interviews were conducted to eight key informants set by snowball sampling. Qualitative approach to case studies by following three stages of analytical techniques from Strauss & Corbin, namely open coding, axial coding, and selective coding. The results obtained are in the form of four propositions, namely: Strengthening the commitment of the taxman, increasing taxpayer compliance, potentially boosting tax revenues as a sign of successful implementation of tax reform; Improving the economy, the adjustment of tax reform, supported by sophisticated management information systems, are suspected to be able to encourage the strengthening of tax reform implementation; Professional management, supported by good marketing, as well as the implementation of appropriate strategies, is suspected to be able to encourage the strengthening of tax reform implementation; as well as intensive socialization, fair law enforcement, reduced constraints are suspected to be able to encourage strengthening the implementation of tax reform.Keywords: Marketing, Socialization, Reform, Management Information Systems, Economy, Compliance, Acceptance, Management, Law, Commitment, Strategy, Constraints. ABSTRAK Tujuan penelitian adalah untuk mendapatkan bukti empiris berupa proposisi dan existing model tentang eksplorasi faktor kendala dan strategi implementasi reformasi perpajakan guna mendorong peningkatan penerimaan pajak dan kepatuhan wajib pajak. Wawancara intensif dilakukan kepada delapan key informan yang ditetapkan secara snowball sampling. Pendekatan kualitatif studi kasus dengan mengikuti tiga tahapan teknik analisis dari Strauss & Corbin, yakni open coding, axial coding, dan selective coding. Hasil yang diperoleh berupa empat proposisi, yakni: Menguatnya komitmen petugas pajak, meningkatnya kepatuhan wajib pajak, berpotensi mendongkrak penerimaan pajak sebagai tanda suksesnya implementasi reformasi perpajakan; Membaiknya perekonomian, adanya penyesuaian reformasi perpajakan, didukung sistem informasi manajemen yang canggih, diduga mampu mendorong penguatan implementasi reformasi perpajakan; Manajemen yang profesional, didukung marketing yang baik, serta penerapan strategi yang tepat, diduga mampu mendorong penguatan implementasi reformasi perpajakan; serta Sosialisasi yang intensif, penegakan hukum yang adil, kendala yang ada berkurang diduga mampu mendorong penguatan implementasi reformasi perpajakKata kunci: Marketing, Sosialisasi, Reformasi, Sistem Informasi Manajemen, Ekonomi, Kepatuhan, Penerimaan, Manajemen, Hukum, Komitmen, Strategi, Kendala.